Bausteine einer Korpusgrammatik des Deutschen: Bd. 1 (2020) - Konopka, Marek; Wöllstein, Angelika; Felder, Ekkehard (Bausteine einer Korpusgrammatik des Deutschen, 2020)
Bausteine einer Korpusgrammatik des Deutschen ("Building blocks towards a corpus grammar of German") is a series presenting corpus linguistic studies on German grammar conducted at the Leibniz Institute for the German Language in Mannheim (IDS). Using state-of-the-art corpus linguistic methodology, the series aims to capture the diversity and variability of German grammar at a high resolution. At the same time, it aims to ensure the study results are verifiable. Issue by issue, the series will add "building blocks" for a new, consistently corpus-based grammar of German. In addition to the peer-reviewed texts, which are written in the style of grammar chapters, the series publishes the results of statistical analyses and, for selected topics, the underlying data sets.